Evolution of genome space occupation in ferns: linking genome diversity and species richness. (14th July 2021) - Fujiwara, Tao; Liu, Hongmei; Meza-Torres, Esteban I; Morero, Rita E; Vega, Alvaro J; Liang, Zhenlong; Ebihara, Atsushi; Leitch, Ilia J; Schneider, Harald
Abstract: Background and Aims: The dynamics of genome evolution caused by whole genome duplications and other processes are hypothesized to shape the diversification of plants and thus contribute to the astonishing variation in species richness among the main lineages of land plants. Ferns, the second most species-rich lineage of land plants, are highly suitable to test this hypothesis because of several unique features that distinguish fern genomes from those of seed plants. In this study, we tested the hypothesis that genome diversity and disparity shape fern species diversity by recording several parameters related to genome size and chromosome number. Methods: We conducted de novo measurement of DNA C-values across the fern phylogeny to reconstruct the phylogenetic history of the genome space occupation in ferns by integrating genomic parameters such as genome size, chromosome number and average DNA amount per chromosome into a time-scaled phylogenetic framework. Using phylogenetic generalized least square methods, we determined correlations between chromosome number and genome size, species diversity and evolutionary rates of their transformation. Key Results: The measurements of DNA C-values for 233 species more than doubled the taxon coverage from 2.2 % in previous studies to 5.3 % of extant diversity. The dataset not only documented substantial differences in the accumulation of genomic diversity and disparity among the major lineages of ferns but also supported the predicted correlation between species diversity and the dynamics of genome evolution. Conclusions: Our results demonstrated substantial genome disparity among different groups of ferns and supported the prediction that alterations of reproductive modes alter trends of genome evolution. Finally, we recovered evidence for a close link between the dynamics of genome evolution and species diversity in ferns for the first time.